Konsep Kurikulum Ramah Anak di Lembaga Pendidikan Anak Uisa Dini - Agus Niada Lawolo; Esra Pakpahan; Ester Gustina Wati Sihotang; Glori Sonnya Simanugkalit (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Implementing a child-friendly curriculum in PAUD (Early Childhood Education) institutions is an important approach to ensure children's learning experiences are not only academically effective, but also pay attention to their holistic development. This curriculum emphasizes play as a key element, allowing children to learn naturally and joyfully while developing social, cognitive and motor skills. The importance of a differentiated approach is also emphasized, ensuring that each child receives support according to their needs. The integration of moral values and character as well as the wise use of technology are also part of this curriculum. Collaboration between PAUD institutions, teachers, parents and communities is important to create a supportive learning environment. With holistic, integrated and sustainable steps, implementing a child-friendly curriculum can provide a meaningful learning experience and support children's overall development.